Pemanfaatan Platform CETTAR Sebagai Inovasi Layanan dalam Mengimplementasikan Good Governance di Jawa Timur - Labib, Muhammad Mughni (Universitas Nahdlatul Ulama Blitar, 2024)
Public services are the main indicator of government performance. A step to overcome the weaknesses of public services is the development of digital-based public services. In order to build a strong East Java government structure, the public service innovation of the CETTAR program is examined in this article. Through the website and application, someone can access the CETTAR East Java application. A library research approach was used in this research. Data was collected for research using documentation methods and content analysis techniques for online data monitoring. A study of relevant literature, research and journals was carried out for this research. This study intends to learn more about the innovation of the CETTAR program and the challenges of implementing trustworthy governance. Based on research findings, this program has been running quite effectively, but there are still challenges in the form of a lack of socialization and strategies that are only half-implemented. It is hoped that the general public can benefit from this research, especially the people of East Java and it can be a means of increasing awareness about how important it is to realize good governance, because it cannot be realized without public service innovation. On the other hand, this research is expected to provide advice to government stakeholders. related to continuing to stimulate performance in order to achieve maximum targets.